La bicyclette comme moyen de transport au Canada : le cas de la région de la Capitale nationale. - Moreau, Laurent. (University of Ottawa (Canada), 1994)
A large database was produced from a survey held in the summer of 1991 on commuters who cycle to work in downtown Ottawa. Social reasons underly this type of commuting which a majority of cyclists practice seven months a year. Cyclists perceive acutely the dangers of sharing the road with motor vehicles therefore are pushed to demand more bike paths despite the fact that well-thought integration to the entire road system is preferable. The potential of the bicycle as a transportation means in an urban environment is demonstrated. However research should be initiated to design a bicycle better suited to the Canadian climate.
Keywords: Geography.